2019
DOI: 10.1021/acsami.9b05785
|View full text |Cite
|
Sign up to set email alerts
|

Self-Supported Hierarchical IrO2@NiO Nanoflake Arrays as an Efficient and Durable Catalyst for Electrochemical Oxygen Evolution

Abstract: Although traditional IrO2 nanoparticles loaded on a carbon support (IrO2@C) have been taken as a benchmark catalyst for the oxygen evolution reaction (OER), their catalytic efficiency, operation stability, and IrO2 utilization are far from satisfactory due to the inferior powdery structure and inevitable corrosion of both IrO2 and C under the oxidizing potentials. Here, a rational design of a self-supported hierarchical nanocomposite, composed of IrO2@NiO nanoparticle-built porous nanoflake arrays vertically g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…The existing strategies can be classified into three major categories: (1) the introduction of specific components to generate composites, including those containing conductive and acid‐resistant materials as supports, alloys with nonprecious metals (Ni, Co, Cu, etc. ), core‐shell structures and various mixed metal oxide composites; (2) controlling special morphologies to create and expose additional active sites, such as two‐dimensional catalysts featuring ultrathin sheets, needles, or nanowires or three‐dimensional structures featuring abundant mesopores; (3) the formation of particular structures including amorphous IrO x , SrIrO 3 perovskite, SrTi 0.67 Ir 0.33 O 3 perovskite, Y 2 Ir 2 O 7 pyrochlore and Y 2 Ru 2 O 7‐δ pyrochlore . Despite these advances, the overpotential at 10 mA cm −2 is generally ∼300 mV and the catalysts are typically stable for less than 10 h. Their catalytic activity and stability can be even worse when Ir contents are reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The existing strategies can be classified into three major categories: (1) the introduction of specific components to generate composites, including those containing conductive and acid‐resistant materials as supports, alloys with nonprecious metals (Ni, Co, Cu, etc. ), core‐shell structures and various mixed metal oxide composites; (2) controlling special morphologies to create and expose additional active sites, such as two‐dimensional catalysts featuring ultrathin sheets, needles, or nanowires or three‐dimensional structures featuring abundant mesopores; (3) the formation of particular structures including amorphous IrO x , SrIrO 3 perovskite, SrTi 0.67 Ir 0.33 O 3 perovskite, Y 2 Ir 2 O 7 pyrochlore and Y 2 Ru 2 O 7‐δ pyrochlore . Despite these advances, the overpotential at 10 mA cm −2 is generally ∼300 mV and the catalysts are typically stable for less than 10 h. Their catalytic activity and stability can be even worse when Ir contents are reduced.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the diameters of the semicircles for IrO x /Ir were compared to that of Ir, and it was confirmed that semicircles were connected to the OER kinetics. Therefore, EIS data also indicated high catalytic activity of IrO x /Ir in the OER performance [6, 10k,o] …”
Section: Resultsmentioning
confidence: 91%
“…All hollow HEA nanoparticles were synthesized using the desired MCl x H y precursors (0.05 m) at equivalent ratios and citric acid (0.10 m) [8,9,24,27,[31][32][33][34][35][36][37][38][39][40][41][42][43] and this present work. The hollow HEA catalyst stands out with one of lowest mass loading but the highest current density for Li-O 2 battery cycling due to its hollow structure.…”
Section: Methodsmentioning
confidence: 99%
“…We found this to be indeed the case, with the specific mass loading not only appearing to be among the lowest in the literature to promote cell operation with a lifetime of over 30 cycles, but the operational current density of the hollow HEAs also outperformed reported cathode catalysts for Li-O 2 battery operations, to the best of our knowledge (Figure 4b). [8,9,24,27,[31][32][33][34][35][36][37][38][39][40][41][42][43] This result indicates that with the use of the hollow nanoparticle design, the required total mass loading of the catalyst for the operation of electrochemical devices can be significantly reduced.…”
Section: −1mentioning
confidence: 99%